Hayseed Capitalists: Private Bankers in Ontario - Thorning, Stephen Edward (My University, 1994)
The structure of the Canadian banking system, and the establishment of strong charter banks at a relatively early stage, have overshadowed banking institutions that operated outside the chartered system. The non-chartered or private banks can be categorized into three groups: the joint stock banks of the 1830s, the urban private bankers who appeared in the 1850s and after, and the small-town private banks of the post-1868 period. All three types of private banks were established to fill perceived niches in the chartered bank system. Those of the 1830s possessed an anti-establishment, hinterland bias. The urban private bankers specialized in savings and foreign exchange transactions, and often branched out into insurance, debentures, and ultimately stocks and bonds. The small town private banks began and prospered when the needs of small hinterland communities outpaced the inclination and ability of chartered banks to provide them with banking facilities. Unlike the urban private bankers, those in small towns offered a full range of banking services, and they often acted as insurance and real estate agencies as well. They appealed strongly to local loyalties, and operated more cheaply than chartered bank branches. In most cases these small-town private banks were supported by the chartered banks with loans, and with access to the cheque clearing system, though chartered banks varied considerably in their attitude to them. Locally, private banks recirculated a community's savings, and deployed the proprietor's capital in local enterprises. Like most industries, private banking displayed easily recognizable phases of rapid (and often reckless) growth, maturity, and decline. At its peak, with more than 150 firms, private banking dominated in non-urban areas of Ontario. Private banks constituted the majority of banking offices in the province in the 1880s and early 1890s, and in aggregate, their volume of business equalled that of a major chartered bank. The demise of private banking resulted from internal efficiencies in the chartered bank system that facilitated the profitable operation of small-town branches, a greater confidence by the public in chartered banks, and a reduced sphere of operation for private banks as an integrated financial system gradually displaced semi-autonomous local economics. In a broad sense, Ontario private banks represent a phase in the establishment of extensive branch systems by the chartered banks. Due to their relationships with chartered banks, to the structure of the Canadian banking system, and to the nature of economic development in the hinterland of the province, Ontario's private banks have no precise parallel elsewhere.
Keywords: History; History